A novel SEA‐based haptic force feedback master hand controller for robotic endovascular intervention system. Issue 5 (21st June 2020) - Wang, Kundong; Mai, Ximing; Xu, Haijin; Lu, Qingsheng; Yan, Weiwu
Abstract: Robotic Endovascular Intervention System (REIS) has been a focused and interesting area in robot‐assisted telesurgery. While, haptic feedback is the latest advancing study in interventional robots. Few systems with haptic feedback are commercialized due to accuracy, instantaneity, and the lack of surgeon previous experience on interventional surgery. In this article, a novel haptic force feedback master hand controller system is proposed to solve the problems. A SEA (Series Elastic Actuators)‐based mechanism is designed to provide feedback force with high force/torque fidelity, low impedance, and inertia. Also, the handle of the mechanism is similar to the catheter, making the surgeon operate the telesurgery with his experience. The control model of the system is built, and PID algorithms are explored to realize the motion control. PID parameters are optimized for fast response time and stability. The experiments and results demonstrate that the master hand controller system has maximum feedback force relative error of 3%, instantaneity of 0.89 second and tracking performance of 9 Hz frequency 3 dB bandwidth.